Management of the Da'wah of the Muhammadiyah Regional Leaders of Sinjai Regency during the Covid-19 Pandemic - Mursak Mursak; Kiki Rasmala Sani (Jurnal Ad'ministrare, 2021)
The impact Covid-19 pandemic is very big when we look at it from the quality and quantity side, where previously the community generally prayed in congregation in the mosque both in terms of quantity, but during the Covid-19 pandemic, we can see that in the field it has fallen greatly in terms of quantity.This study aims to determine the management carried out by the Muhammadiyah Regional Leaders (PDM) of the Sinjai Regency in conducting Da'wah during the Covid-19 Pandemic. The method used is qualitative research methods and data collection techniques through observation, interviews, and documentation. Data analysis techniques include data reduction, data verification, and concluding, the results of this study indicate that Da'wah Planning, Muhammadiyah Regional Leaders carry out Da'wah planning virtually by involving several Muhammadiyah Business Charities in Sinjai Regency. Also, during this pandemic in terms of quantity, there were more recitation participants than before the pandemic. Then in terms of controlling Da'wah, the PDM of the Sinjai Regency carried out control, namely evaluating in terms of the implementation of da'wah by always synergizing and coordinating with all Muhammadiyah charities in Sinjai Regency, starting from Ortom, Higher Education to Branch Leaders in each of the existing branches.